Achievement goals, learning strateges and language achevement among peruvian high school students - Matos Fernández, Lennia (2007)
We used an achievement goal framework to study the role of motivation in the academic context of a Peruvian sample of 8 th to 10 th grade high school students (N = 1505). The purpose of this cross-sectional study was to examine the relationship between students' achievement goals, their use of learning strategies and their academic achievement. Multiple Hierarchical Regressions Analyses identified, as predicted, positive effects of mastery goals, including more use of learning strategies and higher academic achievement, and negative effects of performance avoidance goals, including lower academic achievement. Mixed results were found for pursuing performance approach goals, which predicted a greater use of learning strategies, but were unrelated to academic achievement. The present findings support the external validity of achievement goal theory in a sample of students from a culture that is understudied in the achievement goal literature in particular and the motivational literature in general.